Peningkatan Kualitas Pelayanan Birokrasi di Kantor Camat Watang Pulu Kabupaten Sidrap - Erfina Erfina; Irawan Fattah (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract The purpose of this research was to determine the improvement of bureaucracy service quality at Watang Pulu District Office in Sidenreng Rappang, along with the influencing factors that. The method used was qualitative descriptive method, that aimed to provide an overview about the efforts to improve the quality of bureaucracy services in governmental support at Watang Pulu District Office in Sidenreng Rappang using a survey approach. The population in this study were all apparatus at Watang Pulu District Office and its people, to conclude 45 people and all of them were accounted as sample. The results obtained from the calculation of factors that affect the service quality were (1) awareness factor was rated 3,06, (2) rules factor was rated 3,02, (3) organizing factor was rated 2,68, (4) ability factor was rated 3,08, and (5) service facilities was rated 2,66. These results concluded the improvement of bureaucracy service quality at Watang Pulu District Office in Sidenreng Rappang was in good category at a rate of 2,9.